Enhanced Super‐Rotation Before and During the 2018 Martian Global Dust Storm - Kylash Rajendran; Stephen R. Lewis; James A. Holmes; Paul M. Streeter; Anna A. Fedorova; Manish R. Patel (Geophysical Research Letters, 2021)
Abstract Super‐rotation affects—and is affected by—the distribution of dust in the martian atmosphere. We modeled this interaction during the 2018 global dust storm (GDS) of Mars Year 34 using data assimilation. Super‐rotation increased by a factor of two at the peak of the GDS, as compared to the same period in the previous year which did not feature a GDS. A strong westerly jet formed in the tropical lower atmosphere, with strong easterlies above 60 km, as a result of momentum transport by thermal tides. Enhanced super‐rotation is shown to have commenced 40 sols before the onset of the GDS, due to dust lifting in the southern mid‐latitudes and tropics. The uniform distribution of dust in the tropics resulted in a symmetric Hadley cell with a tropical upwelling branch that could efficiently transport dust vertically; this may have significantly contributed to the rapid expansion of the storm.